Partial Androgen Insensitivity Syndrome: aaPartial androgen insensitivity syndrome: An infrequent cause of pubertal gynecomastian infrequent cause of pubertal gynecomastia - yerawar, chaitanya; Shaikh, Anees Ahmed Fazle Ahmed; Pandit, Aditi; Deokar, prerana (Indian Journal of Case Reports, 2022)
Gynecomastia refers to an enlargement of the breast tissue in males, caused by proliferation of glandular breast tissue.1 Pubertal gynecomastia is a common condition seen in around 60% of the adolescent boys and in most of the cases it resolves spontaneously over 1 - 2 years.1 Persistent pubertal gynecomastia is less frequent and can be associated with underlying pathological condition. We report a case of persistent pubertal gynecomastia with micropenis and bifid scrotum due to partial androgen insensitivity syndrome (PAIS).